Connecting knowledge: First-year health care students' learning in early interprofessional tutorials. - Törnqvist, Tove; Ekstedt, Mattias; Wiggins, Sally; Abrandt Dahlgren, Madeleine (Journal of Interprofessional Care)
Collaboration across professional boundaries is an essential aspect of health care, and interprofessional education (IPE) is a common way to help increase students' collaborative abilities. Research on how and when IPE should be arranged in a curriculum remains, however, inconclusive. How students actually develop interprofessional competencies have been difficult to demonstrate and is still an under-researched area. Studying IPE in context is therefore important to understand its full complexity. This paper examines how students work with scenarios from professional health care contexts when learning together in interprofessional problem-based learning tutorials during the first year of undergraduate education. The data are video-recorded tutorials of students from medicine, nursing, occupational therapy, speech and language pathology, and physiotherapy programmes. The analysis focuses on students' discussing their readings of the literature. Drawing on "Communities of Practice," findings show that students discuss and connect professional knowledge, with "brokers" (the tutors) and "boundary objects" (scenarios) supporting the emergence of students' professional knowledge. The scenarios, as boundary objects, also enabled the students to turn into brokers themselves. The paper contributes to research on interprofessional learning and offers support for implementing IPE in the early stages of undergraduate education.